CULTURAL, MORPHOLOGICAL AND BIOCHEMICAL VARIATIONS OF ALTERNARIA SOLANI CAUSING DISEASES ON SOLANACEOUS CROPS - TANYA R. MARAK,; BHARAT SINGH AMBESH,; SRIKANTA DAS, (The Bioscan, 2014)
Alternaria solani is an economically important pathogen causing diseases on Solanaceae crops. Significant morphological variations in length and breadth of conidia, numbers of horizontal, vertical and oblique septations were observed in the test isolates. The conidia varied from 20.68-43.10 x 10.53-17.99μm in brinjal, 19.86-43.73 x 7.52-13.05μm in chilli, 21.5-33.21 x 8.03-17.85μm in potato and 30.31-75.47 x 7.26-27.42μm in tomato isolates. Variability with respect to cultural characters showed that brinjal, tomato and potato isolates produce cottony mycelia growth in all the tested media. Maximum growth was recorded on PDA for chilli and potato (93.33mm and 95.00mm respectively), CDA for brinjal (85.33mm) and PCA for tomato (87.00mm). Isozyme tested in PAGE showed that tomato produces three bands and potato, brinjal and chilli produces four bands each for α- esterase. For β- esterase tomato and potato produces two bands each and chilli produces three bands. The cluster analysis of morphological characters showed that brinjal, tomato and potato were in same cluster and in isozyme studies potato, chilli and brinjal were in same and tomato in different cluster. Existence of variation among different Alternaria isolates is evident from the results obtained.